Stabilization of Carboxylate Surface Species on Pd(111) - Florencia Calaza; Wilfred T. Tysoe; Darío J. Stacchiola (Adsorption Science & Technology)
The stabilization of formate and acetate surface species on Pd(111) has been studied by temperature-programmed desorption and infrared reflection absorption spectroscopy (IRRAS). In addition to the previously reported stabilization of carboxylate species by the pre-adsorption of oxygen, an even bigger stabilizing effect was observed upon the adsorption of carbon monoxide onto formate- and acetate-covered surfaces. The presence of carbon monoxide delays the decomposition of carboxylate species by blocking surrounding sites. Proper use of co-adsorbed species could help to improve selectivity or activity in heterogeneous catalytic reactions.